Against Sexual Violence in the Museum: Art, Curating, and Activism - Perry, Lara; Krasny, Elke (Journal of Cultural Analysis and Social Change, 2022)
Depictions of sexual violence are frequently found in the collections and displays of art museums, and material that represents and affirms violence against women often is displayed unchallenged. This article poses questions about how the presence of this material has been addressed in the relations between feminist activism against sexual violence, art made by artists responding to and participating in feminist activism, and the curatorial activities that have arisen to address the challenges that these activities present to art museums. The chapter investigates the 2021 exhibition Titian: Women, Myth and Power at the Isabella Stewart Gardner Museum and its handling of themes of rape in the central exhibit, Titian’s Rape of Europa; the history of themes of rape in feminist art since the 1970s and in exhibitions of this art that have taken place in museums in the last two decades; and curatorial engagements with sexual violence and rape in recent art exhibitions in the US and in the UK. The article argues that new strategies for the presentation and interpretation of artworks dealing with sexual violence are needed for museums to redress the patriarchal and colonial presence of sexual violence in their collection.
Keywords: Art Curating; Fine Arts; Museum; Museum Violence; Myriam; Rape; Sexual Violence; Visual activism

What else can a crush become: working with arts-methods to address sexual harassment in pre-teen romantic relationship cultures - Huuki, Tuija; Kyrölä, Kata; Pihkala, Suvi (Gender and Education, 2022)
Keywords: Myriam

Re-Cognizing Harassment with the Arts - Babulski, Timothy (Phenomenology & Practice, 2022)
Absent mechanisms of restorative justice, victims of sexual harassment, particularly those within the LGBT+ community that are already frequent targets of relational aggression, are unlikely to either report or reckon with the consequences of inappropriate workplace behaviors and discrimination. Written from the perspective of a masculinized bisexual whose encounter with a pervasive culture of sexual harassment and psychological abuse provoked suicidal ideation, this paper employs the artistic practices of illustration as a means of first re-cognizing and recognizing phenomena, a Ricœurean construct of narrative and a palimpsest of multivocal text and images to evoke the lived experience of harassment and an analytic layer to invoke the phenomenon. By drawing, writing, and thinking through the phenomenon, the marriage of artistic and phenomenological approaches allows both researcher and reader to confront the ‘painful truths’ that otherwise resist easy analysis.
Number: 2
Keywords: LGBTIQ; Myriam; Safe spaces; Teaching arts; Visual arts